2019
DOI: 10.1029/2018ja025707
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Simulations of Solar Radio Emissions

Abstract: Solar radio emissions are electromagnetic waves emitted in the solar wind as a consequence of electron beams accelerated during solar flares or interplanetary shocks such as interplanetary coronal mass ejections. Different physical mechanisms have been suggested to describe their origin. A good understanding of the emission process would enable to infer the kinetic energy transferred from accelerated electrons to radio waves. Even if the electrostatic case has been extensively studied, full electromagnetic sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 34 publications
(40 reference statements)
1
39
0
2
Order By: Relevance
“…Analytical models and numerical simulations have been developed to interpret these space observations. Recently, three-dimensional EM particle-in-cell simulations tackled several questions regarding the efficiency of the conversion process from LW to EM waves, and the emission pattern of the EM waves [8,9]. These models and simulations yet remain to be confronted with experimental data.Laboratory experiments provide a complementary and powerful method to study the fundamental mechanisms of wave coupling.…”
mentioning
confidence: 99%
“…Analytical models and numerical simulations have been developed to interpret these space observations. Recently, three-dimensional EM particle-in-cell simulations tackled several questions regarding the efficiency of the conversion process from LW to EM waves, and the emission pattern of the EM waves [8,9]. These models and simulations yet remain to be confronted with experimental data.Laboratory experiments provide a complementary and powerful method to study the fundamental mechanisms of wave coupling.…”
mentioning
confidence: 99%
“…Both studies were able to produce electrostatic and electromagnetic waves through plasma instabilities. Henri et al (2019) found weaker electron beams produced radio waves that were more forward directed at the source, whilst larger beam densities widened the Langmuir wave spectrum, leading to a larger available angular spread of radio emission. The validity of the weak turbulence approximation has been analyzed using PIC code both for 1D (Ratcliffe et al, 2014a) and 2D (Lee et al, 2019) weak turbulence codes.…”
Section: Electron Beam Propagationmentioning
confidence: 96%
“…When electron beams become unstable, it has been the focus of many recent theoretical works how density inhomogeneities in the background plasma influence subsequent Langmuir wave growth, electromagnetic emission and the development of the electron distribution function. Studies are typically carried out either in one spatial location (e.g., Ratcliffe and Kontar, 2014;Krafft et al, 2015;, in a small spatial box (e.g., Thurgood and Tsiklauri, 2015;Volokitin and Krafft, 2018;Henri et al, 2019;Krafft and Volokitin, 2020) or over distance comparable to the solar corona or longer (e.g., Li et al, 2012;Reid and Kontar, 2013, 2017bLoi et al, 2014;Ratcliffe et al, 2014b). Each of these different approaches has their own advantages and disadvantages and are used based upon the focus of the relevant study.…”
Section: Electron Beam Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…Генерация электромагнитного (ЭМ) излучения вблизи гармоник плазменной частоты в процессе коллективного взаимодействия плазмы с потоками электронов является одной из фундаментальных проблем физики плазмы, которая в настоящее время активно изучается как применительно к солнечным радио [1][2][3] и субтерагерцовым [4; 5] вспышкам, так и в связи с разработкой мощного источника терагерцового излучения [6; 7]. В терагерцовой области спектра методы, основанные на коллективном возбуждении плазменных колебаний и их дальнейшей конверсии в электромагнитные волны, имеют ряд преимуществ по сравнению со стандартными методами вакуумной электроники.…”
Section: Introductionunclassified